Iodine budget in forest soils: Influence of environmental conditions and soil physicochemical properties. (June 2019) - Roulier, Marine; Coppin, Frédéric; Bueno, Maïté; Nicolas, Manuel; Thiry, Yves; Della Vedova, Claire; Février, Laureline; Pannier, Florence; Le Hécho, Isabelle
Abstract: Due to its longevity, radioisotope 129 I is a health concern following potential releases in the environment which raises questions about residence and exposure times relevant for risk assessments. We determined 127 I concentrations (as a surrogate for 129 I) in a series of French forest soils (i.e. litters, humus and mineral soils) under different vegetation and climate conditions in order to identify the major processes affecting its accumulation and persistence in the soil column. The input fluxes linked to rainfall, throughfall and litterfall were also characterized. Main results obtained showed that: (i) rainfall iodine concentrations probably influenced those of litterfall through absorption by leaves/needles returning to the ground; (ii) throughfall was the major iodine input to soils (mean = 83%), compared to litterfall (mean = 17%); (iii) humus represented a temporary storage of iodine from atmospheric and biomass deposits; (iv) iodine concentrations in soils depended on both the iodine inputs and the soil's ability to retain iodine due to its organic matter, total iron and aluminium concentrations; (v) these soil properties were the main factors influencing the accumulation of iodine in the soil column, resulting in residence times of 419–1756 years; and (vi) the leaching of iodine-containing organic matter dissolved in soil solution may be an important source of labile organic iodine for groundwater and streams. Highlights: Measurement of I concentrations in French forest soils (litterfall, humus and soil). Rainfall iodine concentrations probably influenced those of litterfall. Throughfall was the major iodine input to soils compared to litterfall. Major role of organic matter, iron and aluminium in iodine persistence in soils. Concentrations of I in forest soils varied with vegetation and climatic conditions.